THE ROLE OF VOCATIONAL GUIDANCE AND COUNSELLING IN ENHANCING SUSTAINABLE DEVELOPMENT AMONG SECONDARY SCHOOL STUDENTS IN NIGERIA (Journal of Guidance and Counselling Studies, 2020)
This paper examined the role of vocational guidance in enhancing sustainable development among secondary school students in Nigeria. The paper was able to discuss some of the problems secondary school student used to encounter in the course of choosing their vocational careers. It also explained how vocational guidance and counselling will help the students to come out of such problems.  The meaning of sustainable development were discussed as well as the aims and objective of vocational guidance. The roles of vocational guidance in sustaining development were equally explained. Recommendations were made among which are that the federal, state and local governments should provide a clear vision and mission for Vocational Guidance and Counselling Education in Nigeria. They should also increase funding of Vocational Guidance and Counselling Education programmes at all levels of education among others.
Keywords: Vocational; Guidance; Counselling; Education; Sustainable Development